Mechanisms to Hold ISIS Gangs Accountable for the Cultural Genocide in Iraq - Abdullah, Gufran; Abdul Ameer, Husam (Journal of Legal Sciences, 2023)
Terrorist organizations have played a major role in annihilating cultural heritage in Iraq, and we study the terrorist gangs of ISIS. In June 2014,ISIS gangs launched a fierce war, attacking almost all ethnic and religious sects, in the midst of that, targeting cultural heritage sites. The destruction of cultural heritage by terrorist gangs is not a byproduct of violence, but a carefully planned and documented intervention. In fact, the cultural genocide committed by ISIS criminals in Iraq, as Well as being crimes in accordance with the Iraqi Penal Code, the Anti-Terrorism Law and the Antiquities and Heritage Law, amount to International Crimes. From this point of view, this research presents the attacks committed by ISIS criminals against the cultural heritage in Iraq in the first topic, and in the second section, We Will show the mechanisms available to hold ISIS accountable for these attacks.